2014
DOI: 10.4103/0976-237x.142809
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of cervical vertebrae morphology and correlation of cervical vertebrae morphometry, cervical spine inclination and cranial base angle to craniofacial morphology and stature in an adult skeletal class I and class II population

Abstract: Objective:The study was carried out to compare the morphometry of the cervical column between adult Class I and Class II individuals and between gender and to analyze the correlation between the cervical column morphology, the cranial base angle, the craniocervical inclination with craniofacial morphology and stature of Angles Class I and Class II individuals.Materials and Methods:The data for this institutional retrospective study were systematically selected according to the specified inclusion and exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The facial growth pattern (anterior or posterior rotation) can lead to vertical craniofacial disproportions, i. e. deep or open bite, but it also affects the sagittal relationship between the jaws and can cause potential disproportions in that plane. Previous studies have confirmed the impact of both the vertical [9][10][11][12][13] and the sagittal parameters of the craniofacial system [4,[10][11][12][13][14][15][16][17][18] on the cervicovertebral morphology.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The facial growth pattern (anterior or posterior rotation) can lead to vertical craniofacial disproportions, i. e. deep or open bite, but it also affects the sagittal relationship between the jaws and can cause potential disproportions in that plane. Previous studies have confirmed the impact of both the vertical [9][10][11][12][13] and the sagittal parameters of the craniofacial system [4,[10][11][12][13][14][15][16][17][18] on the cervicovertebral morphology.…”
Section: Introductionmentioning
confidence: 79%
“…The morphology of the cervical spine and the craniofacial system is related to a variety of factors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The influence of different facial growth patterns on the cervicovertebral morphology remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Singla et al [9] have established that the superior facets are inclined by a mean of 69.3° in the coronal plane and the inferior facets by 42.1° in the sagittal plane. There is scant information on the missing values of the facet orientation along the other Cartesian co-ordinates [10,11]. Moreover, little emphasis if any at all, has been laid on the clinical and mechanical import of this information (more attention has been paid to the feasibility of screw trajectory within the bone) [12-19].…”
Section: Anatomical Featuresmentioning
confidence: 99%
“…The cervical spinous process is part of the vertebrae that provides muscle attachment for some muscles in the neck, back, and upper limb. They are important surface landmarks and play a role in screw placement or implants in the cervical spine [3][4][5].…”
Section: Introductionmentioning
confidence: 99%